DIGITAL NATIVES: MEDIA LITERACY, NEWS CONSUMPTION AND HABITS - Nikos Panagiotou; Anna Orfanidou (İmgelem)
People today are in a place where they can produce, consume, store and broadcast news from various sources, media organizations and platforms. There are more options for news consumption than ever before, hence comes the need to comprehend but also compare different news consumption patterns. Following Prensky’s (2001) approach (Digital Natives, Digital Immigrants), this research examines the level of media literacy in the Digital Natives generations (young individuals who have grown up in the digital age) and how said generations consume news. The study focuses on the multiple factors which affect news consumption, distribution and comprehension of mis/disinformation issues, among Digital Natives. A primary quantitative research was conducted and it was based on a closed-ended questionnaire, which was distributed online and was answered by a specimen of 338 adults, born after 1980. Research findings indicate that Digital Natives consider news as strongly affected by political parties. There is a huge surge in the use of digital media, thus traditional means of information, such as newspapers, were found to have a minimum impact on Digital Natives. According to the study findings, they face significant issues regarding trust in news, continuous use of various devices and social media platforms. All these issues influence their information habits and underline the need for tailor-made media literacy approaches.